2023
DOI: 10.1093/plphys/kiad034
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-independent effects of apical dominance induce changes in phytohormones correlated with bud outgrowth

Abstract: The inhibition of shoot branching by the growing shoot tip of plants, termed apical dominance, was originally thought to be mediated by auxin. Recently the importance of the shoot tip sink strength during apical dominance has re-emerged with recent studies highlighting roles for sugars in promoting branching. This raises many unanswered questions on the relative roles of auxin and sugars in apical dominance. Here we show that auxin depletion after decapitation is not always the initial trigger of rapid cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 97 publications
3
28
0
Order By: Relevance
“…In our study, both CTK content and its biosynthetic genes were found to increase after trimming, especially at the 1st node. This is consistent with ndings in pea, where CTK levels were signi cantly enhanced at the upper nodes after decapitation (Cao et al 2023). Therefore, the accumulation of CTK induced by trimming may depend on the distance from the site of trimming.…”
Section: Trimming Increased the Energy Distribution Towards The Tille...supporting
confidence: 91%
“…In our study, both CTK content and its biosynthetic genes were found to increase after trimming, especially at the 1st node. This is consistent with ndings in pea, where CTK levels were signi cantly enhanced at the upper nodes after decapitation (Cao et al 2023). Therefore, the accumulation of CTK induced by trimming may depend on the distance from the site of trimming.…”
Section: Trimming Increased the Energy Distribution Towards The Tille...supporting
confidence: 91%
“…Further evidence for this link comes from analysis of the role of gibberellin (GA) in shoot branching. Bud growth rate is promoted by GA in vegetative pea buds (Cao et al ., 2023). GA modulates PIN2 abundance and trafficking in Arabidopsis roots, and GA biosynthetic and signalling mutants have lower auxin transport (Willige et al ., 2011; Löfke et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts to characterise different stages of bud regulation have led to a two‐phase model of bud outgrowth based primarily on data from pea and rose (reviewed in Beveridge et al ., 2023). The first stage of ‘bud release’ occurs immediately post‐decapitation, regulated in an auxin‐independent manner, followed by a second phase of ‘sustained growth’, during which auxin transport out of the bud would be established (Barbier et al ., 2015; Chabikwa et al ., 2019; Bertheloot et al ., 2020; Cao et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Plant genomes encode very large families of membrane‐localised receptor‐like kinases (RLK) (Monshausen & Haswell, 2013), so it is plausible to suggest that the difference in stomata operation between xerophytes and mesophytes may be related to their functional expression/sensitivity. More recent evidence also suggests that sucrose may operate as a long‐distance signalling molecule, which activates the trehalose‐6‐phosphate signal when transferred from the phloem into the buds, triggering axillary bud outgrowth (Cao et al., 2023).…”
Section: Optimising Stomata Operation Via Aba Sensing and Signallingmentioning
confidence: 99%